Banana Ripening Science and Technology - Thompson, Anthony Keith; Supapvanich, Suriyan; Sirison, Jiraporn; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The technology used to ripen bananas is affected by a wide range of factors, including the cultivar, growing conditions, harvesting method, and maturity at which the fruit are harvested and handled. Various post harvest treatments applied to fruit can also impact ripening. While many textbooks have been dedicated to Musa (bananas and plantains), none have focused exclusively on the ripening process. The commercial ripening of bananas and the chemical changes that occur thereby are considered here in detail. In developed, temperate countries where bananas are imported, successful ripening technologies have evolved. Most bananas, however, are marketed locally in the country where they are grown, and often the ripening technologies used have economic and health implications. This brief offers an in-depth discussion of not only the implications of these technologies, but also of alternative ripening methods and their commercial applications. For an understanding of both the chemical basis by which bananas ripen and the technologies used to control the process, look no further than this essential text.
Ch 1: Introduction -- Ch 2: Preharvest effects -- Ch 3: Fruit ripening -- Ch 4: Postharvest treatments to control ripening -- Ch 5: Initiation of ripening -- Ch 6: Ripening Technology -- Ch 7: Conclusions.
Keywords: Food -- Microbiology; Food science; Chemistry, Organic; Food Microbiology; Food Science; Organic Chemistry